PHILOSOPHICAL VIEWS OF ABU ALI IBN SINA AND NASIRUDDIN TUSI (Scientific journal of the Fergana State University, 2024)
This article compares the philosophical views of Abu Ali ibn Sina  and his follower Nasiruddin Tusi the great thinker of the Early Renaissance, and reveals their significance.